Centenary subjects : race, reason, and rupture in the Americas - McDaniel, Shawn, 1979- (Vanderbilt University Press, 2021)
"The equivocal contours of arielismo-one of the most influential anti-imperialist ideologies, spiritual movements, cultural models, and utopian pedagogies for Latin American youth in an epoch of rampant US interventionism"--